55.8k views
1 vote
Question 19 (4 points)
Saved
2(x + 1) + 2(x - 2) = 3(x-3) + 4​

User RaphaMex
by
5.5k points

2 Answers

4 votes

Answer:

x = - 3

Explanation:

2(x + 1) + 2(x - 2) = 3(x-3) + 4​

2x + 2 + 2x - 4 = 3x - 9 + 4

2x + 2x - 3x = - 9 + 4 - 2 + 4

4x - 3x = - 3

x = - 3

User Andrzej Rehmann
by
5.1k points
6 votes

Answer:

x=-3

solution,


2(x + 1) + 2(x - 2) = 3(x - 3) + 4 \\ or \: 2x + 2 + 2x - 4 = 3x - 9 + 4 \\ or \: 2x + 2x + 2 - 4 = 3x - 5 \\ or \: 4x - 2 = 3x - 5 \\ or \: 4x - 3x = - 5 + 2 \\ x = - 3

Hope this helps...

good luck on your assignment.

User Dineshkumar
by
6.1k points